Effect of Saccharomyces cerevisiae and nitrogen compounds on the fermentation of banana pulp (Musa spp.) - Medina, Juan; Vásquez, Luis; Gómez, Juan; Mendoza, Edwin; Martín, Álvaro; Plua, Jhoan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The use of agro-industrial by-products, such as banana pulp (Musa spp.), represents a sustainable alternative for animal production, reducing costs and improving resource utilization. The study aimed to evaluate the effect of Saccharomyces cerevisiae, urea, and ammonium sulfate on the nutritional value of banana pulp, seeking to optimize its bromatological properties to transform it into a nutritionally viable and sustainable input. A completely randomized experimental design with a factorial arrangement was employed, considering two treatment levels: 1 % Saccharomyces cerevisiae, 0.8 % urea, and 0.1 % ammonium sulfate, and 1.5 % Saccharomyces cerevisiae, 1 % urea, and 0.2 % ammonium sulfate. The aerobic fermentation times studied were 2, 4, and 6 hours. The results showed that the best bromatological quality was achieved at 6 hours with 1 % Saccharomyces cerevisiae, 0.8 % urea, and 0.1 % ammonium sulfate. However, the most economically efficient treatment was obtained with 1.5 % Saccharomyces cerevisiae, 1 % urea, and 0.2 % ammonium sulfate in 4 hours of fermentation, due to its lower energy consumption. These findings highlight the potential of banana pulp treated as a cost-effective and sustainable input, contributing to more efficient animal production systems.